Programa Saúde da Família: supervisão ou "convisão"? Estudo de caso em município de médio porte - Reis, Cláudia da Costa Leite (2004)
This study discusses supervision of the Family Health Program (FHP) in Teresópolis Rio de Janeiro State, Brazil, based on a qualitative case study approach. Considering that supervision is an important tool in health programs management, five main objectives were achieved: analysis of supervisory activities, description of characteristics and working patterns, outlining of FHP supervisor profiles, and identification of subjective factors that could interfere in the supervision process. Finally, supervision was considered as an essential step in program organization and implementation. Information sources were interviews with program supervisors and staff members, observation, and document search. The aim was to identify perceptions, attitudes, values, and tendencies concerning supervision. Thanks to this study, it was possible to discuss participatory supervision in the health area, by providing a more level relationship between participants and their effect on health practices, fostering the autonomy of various players in the supervisory process and fostering program support, both suitable for changes in the Brazilian health care model.